“Roman Textiles” in the Hou Han Shu. A 5 th Century Chinese Vision versus Roman Reality - Żuchowska, Marta (Anabasis. Studia Classica et Orientalia, 2015)
The paper focuses on the interpretation of terms relating to fabrics from Da Qin (Roman Empire) in the Account of Western Regions (Xi Yu Zhuan) of Hou Han shu (The Book of Han), the official chronicle of the Later Han dynasty composed in the middle of the 5 th century AD. A re-examination of the text reveals that Roman textiles as they appear in the Chinese Annals differ greatly from what we know of them in western literary accounts and archaeological remains. Moreover, the argument is made that the primary reason for this misunderstanding is due largely to Chinese philosophy and how the Chinese perceived the world beyond China’s borders.